Study On Time Efficiency of Catches Landing Toward Mooring Time of The Purse Seiner at Fishing Port of Sibolga - Monalisa Berliana Sibarani; Jonny Zain; Syaifuddin Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstrakThis research was conducted from 30 April -14 May 2019 at the Sibolga Fisheries Port. The method used is a survey method. The purpose of this study was to study the level of efficiency of the fish landing time on the mooring fishing purse seiner in the PPNSibolga and the factors that influence it. The results showed that the level of fish landing time efficiency was between 63.77% - 87.58% with an average of 74.38% which meant it was less efficient. There were six independent variables that streamlined the fish landing time according to the amount needed to unload, last long unloading, ship size, pier loading distance, catch, time wasted. with a value (R = 0.877), it means that the independent variable can contribute to the difference in the value of the loading time efficiency of 87.7% and 12.3% of the settings by other independent variables that are not in accordance with this study.Keyword :Fishing port, mooring time, time efficiency, purse seiner